Capacities and Competences for Drug Evaluation in European Neonatal Intensive Care Units: A Survey and Key Issues for Improvement - Elie, Valery; Neyro, Virginia; Ha, Phuong; Aurich, Beate; Leroux, Stephanie; Jacqz-Aigrain, Evelyne (American Journal of Perinatology, 2018)
Background Multicenter neonatal clinical trials aim to provide evidence-based drug evaluation, but recruiting neonates requires collaboration, standard procedures, and trained neonatologists.Methods A questionnaire based on a previous Delphi study was sent to European neonatal intensive care units (NICUs) to collect their research experience and identify areas for improvement.Results Of 247 NICUs,79 (32%) responded: 69 were level III units and 10 were level II units. In level III centers, 62% had medical staff dedicated to research and 65% conducted regular in-house audits. Similarities were observed in the median number of trials per year (level II: 2; level III: 5), Good Clinical Practice training (level II: 78%; level III: 66%), and standard operating procedures (level II: 63%; level III: 71%). Most NICUs had access to scientific advice for trial design, conduct, data management, and regulatory aspects. Involvement of patient advocacy groups was more common in level II units (level II: 75%; level III: 59%). A “quality” score of 34 “quality” research items was calculated for all centers (mean: 23.2 ± 6.2; range: 6–34).Conclusion Research experience and processes vary across Europe. Harmonizing research practices and setting standards will allow building a European neonatal network for effective, safe, and quality neonatal drug development.
Keywords: neonate; intensive care unit; clinical research; good clinical practices; training; procedures